Seasonal variations of zooplankton community in Sina Kolegoan Dam Osmanabad district, Maharashtra, India. - Jadhav, Swati; Borde, Sunita; Jadhav, Dilip; Humbe, Atul (Journal of Experimental Sciences, 2012)
The plankton constitutes the basic food sources of any aquatic ecosystem, which supports fish and other aquatic animals. Zooplankton diversity is one of the most important ecological parameters in water quality assessment. Zooplanktons are good indicators of the changes in water quality because they are strongly affected by environmental conditions & respond quickly to changes in water quality. Zooplankton is the intermediate link between phytoplankton and fish. Hence qualitative and quantitative studies of zooplankton are of great importance.In the present work, we provide quantitative information on the seasonal variations of zooplankton and selected physico-chemical variables a large man-made reservoir in the Osmanabad district during the year June 2009- May 2010. In the study period we have recorded rotifers showed 5 species, Cladocera by 4 species and Copepods represents 2 species where as Ostracoda showed 2 species. Among zooplankton, particularly Cladocera was the dominant group.